2006
DOI: 10.1016/j.ejvs.2005.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sclerotherapy Using Polidocanol Foam: A Controlled Clinical Trial

Abstract: Efficacy of venous sclerosis with foam seems to be greater than with liquid although there is a higher risk of minor secondary effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
14

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 12 publications
0
92
0
14
Order By: Relevance
“…42 43 reported a statistically significant difference at the 5% level between treatment arms for nerve injury, which favoured EVLA over surgery. Only Alos et al 119 reported a statistically significant difference at the 1% level between treatment arms for pigmentation, which favoured LS over FS. Only Carradice et al 86 reported a statistically significant difference between treatment arms for any other adverse event, with fewer incidents of sensory disturbance in the EVLA arm than the surgery arm (2 vs. 13; p = 0.02).…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations
“…42 43 reported a statistically significant difference at the 5% level between treatment arms for nerve injury, which favoured EVLA over surgery. Only Alos et al 119 reported a statistically significant difference at the 1% level between treatment arms for pigmentation, which favoured LS over FS. Only Carradice et al 86 reported a statistically significant difference between treatment arms for any other adverse event, with fewer incidents of sensory disturbance in the EVLA arm than the surgery arm (2 vs. 13; p = 0.02).…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…Twelve trials 42,44,55,81,88,89,90,95,97,98,119,112 reported data on the failure of the initial procedure (i.e. the intervention failed to strip the vein successfully or the vein was not occluded or obliterated, or open segments remained) within the first few days post operation up to 1 month (see Table 11).…”
Section: Failure Of Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar follow-up has also been suggested by several other authors. [12][13][14][15] An ultrasound examination was done a week after therapy showed optimum obliteration of the treated vein in all the cases and also showed no signs of DVT. Thus re-sclerotherapy was not required.…”
Section: Discussionmentioning
confidence: 99%